Original paperCatheter displacement prior to the delivery of high-dose-rate brachytherapy in the treatment of prostate cancer patients - Kawakami, Shogo; Ishiyama, Hiromichi; Terazaki, Tsuyoshi; Soda, Itaru; Satoh, Takefumi; Kitano, Masashi; Kurosaka, Shinji; Sekiguchi, Akane; Komori, Shouko; Iwamura, Masatsugu; Hayakawa, Kazushige (Journal of Contemporary Brachytherapy, 2014)
Purpose : The purpose of this work was to report measured catheter displacement prior to the delivery of high-dose-rate brachytherapy (HDR) in the treatment of prostate cancer. Material and methods: Data from 30 prostate cancer patients treated with HDR brachytherapy were analyzed retrospectively. Eighteen transperineal hollow catheters were inserted under transrectal ultrasound guidance. Gold marker seeds were also placed transperineally into the base and apex of the prostate gland. Five treatment fractions of 7.5 Gy each were administered over 3 days. The patient underwent CT scanning prior to each treatment fraction. Catheter displacement was measured from the pre-treatment CT dataset reconstructed at 1.25 mm slice thickness. Results: Most of catheters were displaced in the caudal direction. Variations of 18 catheters for each patient were small (standard deviations < 1 mm for all but one patient). Mean displacements relative to the apex marker were 6 ± 4 mm, 12 ± 6 mm, 12 ± 6 mm, 12 ± 6 mm, and 12 ± 6 mm from plan to 1st, 2 nd , 3 rd , 4 th , and 5 th fractions, respectively. Conclusions: Our results indicate that catheter positions must be confirmed and if required, adjusted, prior to every treatment fraction for the precise treatment delivery of HDR brachytherapy, and to potentially reduce over-dosage to the bulbo-membranous urethra.